The Councils of the Archipelagos in the basic law of French Polynesia - M Vernaudon C Territoire de law Polynesie Francaise - decision of the Administrative Tribunal of Papeete of 10 May 1994 - Sage, Yves-Louis; Moyrand, A (Victoria University of Wellington Law Review, 1996)
This article is a case note of the judgment of the Administrative Tribunal of Papeete of 18 May 1994, which concerned the illegality of the tariffs applicable to sea transport services. Mr Emile Vernaudon challenged the legality of a government decision which should have been taken after consultation with the councils of the archipelagoes. The author discusses two potential contentious points: a failure to legislate, and a failure to consult.